Inhibitory effects of periwinkle, small and large snails chitins on angiotensin I converting enzyme (ACE) in Nicotine induced hypertension using wistar albino rats (Funded Work) - OSENI, OLATUNDE.A,; OLOYEDE, OMOTADE.I,; ADELEYE, GBENGA.S, (International Journal of Pharma and Bio Sciences, 2018)
This study sought to evaluate the curative potentials of chitin from periwinkle, small and large snails against nicotine induced hypertension. Chitin was extracted from periwinkle and both the snail’s shells and was used in the treatment of nicotine induced hypertensive rats. The plasma, liver, kidney and heart of the rats were obtained and % inhibition of angiotensin I converting enzyme (ACE), SOD activity, MDA were determined using standard methods. Total Cholesterol, HDL-Cholesterol, Aspartate Transaminase (AST) and Alanine Transaminase (ALT) were determined spectrophotometrically. The results of % inhibition of ACE showed that both individual chitin from the shells of the animals and the combination of the three animal chitins produced significant % inhibition of ACE thereby preventing the formation of angiotensin II. The results also revealed the anti-oxidative, anti-lipidemic potentials of these chitins. The results of this study indicate the possibility of utilizing the shells of these animals as alternative, safe and cheaper means of bioactive compounds as ACE inhibitors.